Enhancement Effects of the Terahertz Near-Field Microscopy - Jian Huang; Zhongbo Yang; Dongshan Wei; Chunlei Du; Hong-Liang Cui (Applied Sciences, 2015)
Terahertz near-field detection based and imaging on a nanotip has drawn wide attention following extensive applications of terahertz imaging technologies. Through the local enhanced electric field created by a terahertz nanotip in the near field, it is very likely to attain superior detection sensitivity and higher spatial resolution. This paper simulates the local enhancement effects of the terahertz near-field microscopy using a two-dimension finite difference time domain (2D-FDTD) method. Factors that influence the enhancement effects are investigated and analyzed in detail. Simulation results show that the size of the nanotip apex, the apex-substrate distance, dielectric properties of the substrate and the detected sample, etc., have significant impacts on the electric field enhancement and spatial resolution of the terahertz near-field nanotip, which can be explained from the effective polarizability of the nanotip-sample/substrate system.